Effect of Trivalent Bi Doping on the Seebeck Coefficient and Electrical Resistivity of Ca3Co4O9 - Cho, Jun-Young; Kwon, O-Jong; Chung, Yong Kwon; Kim, Jin-Sang; Kim, Woo-Seok; Song, Kyu Jeong; Park, Chan (SPRINGER, 2015)
We present the effects of trivalent Bi doping on the microstructure and thermoelectric (TE) properties of Ca3Co4O9 (Ca-349). Specimens were prepared by spark plasma sintering (SPS). The lattice parameters of the conducting [CoO2] layer and insulating [Ca2CoO3] layer of Ca-349 were determined using Rietveld refinements of x-ray diffraction (XRD) data. Partial substitution of Bi for Ca did not lead to any change in the misfit ratio of the conducting versus insulating layers. XRD and transmission electron microscopy (TEM)/energy-dispersive spectrometry (EDS) results show the presence of Bi2O3 phase in the grain-boundary region. The Seebeck coefficient (S) increased with increasing Bi content due to the decrease in the hole carrier concentration after Bi doping. As the amount of Bi was increased, the electrical resistivity (rho) initially decreased but then increased with further addition of Bi. Addition of small amount of Bi led to large decrease in electrical resistivity due to the increased amount of Bi2O3 phase in the grain-boundary region. With further increase of Bi addition, the electrical resistivity increased due to the decrease in the hole carrier concentration. Optimum Bi doping not significantly affecting the hole carrier concentration is an effective approach for increasing the Seebeck coefficient and decreasing the electrical resistivity of Ca-349.